If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-2 + -1x) = 0 (-2 * 3 + -1x * 3) = 0 (-6 + -3x) = 0 Solving -6 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 0 + 6 -3x = 0 + 6 Combine like terms: 0 + 6 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| x(b+2)= | | 8r+9=-5.37-6 | | 1.8r+9=5.7-6 | | 9v^2+21v+18=0 | | 10b^2-23bc-5c^2= | | 9s^3+15s^2-36s= | | -2(n-7)-(9+6n)=-9n | | 6s^2-17s+12= | | -4(k+6)-(-3k-6)=-2k | | 3t^2-33t+84= | | -5+2x=5x-4 | | V^4-100= | | 7(x+5)=8x-7 | | (-3)-(-7)+8=a | | (-3)-(-7)+8=a-d | | 75r^2-192= | | (7b-3)-3(2b+4)=-6 | | w^4-64= | | 64w^2-25d^2= | | (-6)-6=a+d | | 16c^2-56c+49= | | 6(x+10)+4=-10(x-10)-9 | | 6=x+11 | | 25w^2+40wp+16p^2= | | 2x-4=-3x+2 | | (-2)+(-8)+(-4)=a+d | | 2x^2-x+254= | | 2x^2+3x=9x^2-3x-3x+1-x^2 | | v^2-19v+18= | | 0=3900x+217-23.49x^2 | | 7x+6x+4+9=3x+5+9x | | 18x^2-42x=0 |